Development of a Recitation Program with Feedback and Reinforcement Questions to Improving Students' Concept - Handy Faishal Rahim; Arif Hidayat; Sutopo Sutopo (Radiasi : Jurnal Berkala Pendidikan Fisika, 2023)
This study aims to develop and determine the feasibility of learning media consisting of a recitation program with feedback and reinforcement questions to improve students' mastery of concepts. The research design used ADDIE which consisted of 5 research stages, namely: 1) Analysis, 2) Design, 3) Development, and 4) Implementation. Based on data analysis, the media validity average value was 3.7. Thus, it can be concluded that the recitation program with feedback and reinforcement questions has a very valid (worthy) category. Based on the results of this research, the development of a recitation program with feedback and reinforcement questions can be used in learning to improving students' Physics concept.